2001
DOI: 10.1099/0022-1317-82-11-2799
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric papillomavirus-like particles expressing a foreign epitope on capsid surface loops

Abstract: Neutralization capsid epitopes are important determinants for antibody-mediated immune protection against papillomavirus (PV) infection and induced disease. Chimeric L1 major capsid proteins of the human PV type 16 (HPV-16) and the bovine PV type 1 (BPV-1) with a foreign peptide incorporated into several capsid surface loops self-assembled into pentamers or virus-like particles (VLP). Binding patterns of neutralizing monoclonal antibodies (MAb) and immunization of mice confirmed (i) that regions around aa 282-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 33 publications
4
59
0
1
Order By: Relevance
“…Several attempts have been made to provide vaccines that are able to overcome B cell tolerance, e.g., by linkage of self-Ags to foreign Th epitopes (14), or by coapplication of strong adjuvants. Recently, antigenic peptides have been fused or cross-linked to the major capsid protein L1 of papillomaviruses (PV), providing self-assembling empty viral capsids or virus-like particles (VLP), that express the foreign peptide on the particle surface in a repetitive and ordered array (15)(16)(17). Immunizations with VLP have induced high-titer and high-avidity (auto)-reactive IgG Ab even without coadministration of adjuvants.…”
Section: Mmunization With Amyloid-␤ (A␤)mentioning
confidence: 99%
See 2 more Smart Citations
“…Several attempts have been made to provide vaccines that are able to overcome B cell tolerance, e.g., by linkage of self-Ags to foreign Th epitopes (14), or by coapplication of strong adjuvants. Recently, antigenic peptides have been fused or cross-linked to the major capsid protein L1 of papillomaviruses (PV), providing self-assembling empty viral capsids or virus-like particles (VLP), that express the foreign peptide on the particle surface in a repetitive and ordered array (15)(16)(17). Immunizations with VLP have induced high-titer and high-avidity (auto)-reactive IgG Ab even without coadministration of adjuvants.…”
Section: Mmunization With Amyloid-␤ (A␤)mentioning
confidence: 99%
“…Sf9 insect cells were infected with baculovirus stocks and lysed, and high-molecular-mass structures were separated by density gradient ultracentrifugation. VLP-containing bands were collected and dialyzed against PBS/0.5M NaCl/0.05% NaN 3 (17,22). BPV1 L1/L2-VLP consisting of wild type (wt) L1 major plus L2 minor capsid proteins were generated in a similar manner (21).…”
Section: Generation Of Recombinant Baculovirus Expressing the A␤ Epitmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that the epitopes recognized by HPV neutralizing monoclonal antibodies (mAbs), which are generally type-specific and conformation-dependent, map to these regions (Christensen et al, 2001;Ludmerer et al, 1996Ludmerer et al, , 1997Ludmerer et al, , 2000McClements et al, 2001;Roden et al, 1997). Furthermore, structural studies of HPV capsomers and VLPs have shown that these divergent sequence regions are surface-exposed (Chen et al, 2000), and other studies have shown that substitution of these regions with non-L1 sequences results in the presentation of foreign epitopes on VLPs (Chackerian et al, 1999;Slupetzky et al, 2001). …”
mentioning
confidence: 99%
“…The two cysteines that participate in the interpentamer disulphide bonding within the virion or in the virion-sized particles are shown in yellow, together with their residue numbers, 175 and 428. (Modis et al, 2002) Some residues in the L1 protein, such as Asp202, Cys175, and Cys428 of HPV16 L1, are very important for VLP formation (Slupetzky et al, 2001), however some residues at the C'-terminus can be truncated and replaced with heterologous epitopes or short polypeptides up to 60 amino acids without disrupting the assembly of VLPs (Paintsil et al, 1996;Müller et al, 1997;Paz De la Rosa et al, 2009). These chimeric VLPs (cVLPs) can induce strong immune responses against not only the inserted epitopes or polypeptides, but also the VLP shell (Freyschmidt et al, 2004;Varsani et al, 2003a;Xu et al, 2006).…”
Section: Structure Of Hpv Capsid and Neutralizing Epitopes On Its Surmentioning
confidence: 99%